Association Between Bullying Victimization and Physical Fitness Among Children and Adolescents [Asociación Entre la Victimización por Bullying y la Condición Física en Niños y Adolescentes] - Garcia-Hermoso, A (Elsevier Doyma, 2019)
Background/Objective: The aim of the study was to analyze the relationship between being bullied and the physical fitness components, and to determine whether a healthy physical fitness level is related with lower victimization in children and adolescents with overweight and obesity compared to unfit overweight/obese peers. Method:The present cross-sectional study included a total of 7,714 youths (9-17 years), categorized as normal-weight or overweight/obese and fit or unfit according to sex-specific handgrip strength and cardiorespiratory fitness (CRF)cut-points. Bullying (physical, verbal, social exclusion, sexual harassment, and cyberbullying)was assessed through the Standard Health Behavior in School-aged Children survey questions. Results:Boys and girls that were categorized as fit (healthy level of CRF)showed lower traditional bullying compared to unfit counterparts. Also, a healthy level of CRF could be a protective factor of traditional bullying among overweight/obese youths compared to unfit overweight/obese peers. Conclusions:CRF is related with lower risk for experiencing traditional bullying in Latino youths with and without obesity, thus emphasizing the role of fitness even among youth with excess of adiposity. © 2019